A multicenter study on the utility and safety of EBUS‐TBNA and EUS‐B‐FNA in children. Issue 10 (3rd May 2016) - Dhooria, Sahajal; Madan, Karan; Pattabhiraman, Vallandramam; Sehgal, Inderpaul Singh; Mehta, Ravindra; Vishwanath, Gella; Srinivasan, Arjun; Sivaramakrishnan, Mahadevan; Mohan, Anant; Mathew, Joseph L.; Kabra, Sushil K.; Guleria, Randeep; et al.
Summary: Background and Aim: Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) and endoscopic ultrasound with an echobronchoscope‐guided fine needle aspiration (EUS‐B‐FNA) are useful modalities in the evaluation of mediastinal lymphadenopathy in adults; however, there is sparse data in children. The aim of this multicenter study is to describe the efficacy and safety of EBUS‐TBNA and EUS‐B‐FNA in children with mediastinal lymphadenopathy of undefined etiology. Methods: Retrospective analysis of consecutive pediatric (<18 years) subjects who underwent EBUS‐TBNA or EUS‐B‐FNA for the evaluation of mediastinal lymphadenopathy. The demographic characteristics, indications, procedural details, pathological, cytological and microbiological diagnosis, diagnostic yield, and complications are presented. Results: Of the 3, 424 EBUS/EUS‐B‐FNA procedures, 67 (1.9%) were performed in the pediatric (3–17 years) population. Of these, 19 (28.4%) were performed in children ≤12 years of age. Overall, EBUS‐TBNA and EUS‐B‐FNA were performed in 53 and 12 subjects, respectively. In two subjects, no significant lymph node was seen on EBUS. The procedure was performed under moderate sedation in spontaneously breathing subjects in 54 (80.6%) instances. An adequate sample was obtained in 60 (92.3%) subjects while a diagnostic sample was obtained in 37 (56.9%) of the 65 subjects. The diagnostic yield was not significantly different ( P  = 0.59) between EBUS‐TBNA (58.5%) and EUS‐B‐FNA (50%). The sensitivity of EBUS‐TBNA/EUS‐B‐FNA was 79.1% and led to a change in diagnosis in 28 (41.8%) subjects. Complications, all minor were encountered in six (8.9%) subjects. Conclusions: EBUS‐TBNA and EUS‐B‐FNA are safe techniques with a good diagnostic yield in the evaluation of children with mediastinal lymphadenopathy.Pediatr Pulmonol. 2016;51:1031–1039. © 2016 Wiley Periodicals, Inc.